Caminhos da docência: um estudo sobre o desenvolvimento profissional docente de uma professora da Educação Básica - Barros, Janailza Moura de Sousa (2024)
Teacher training is a continuous process that takes place throughout teachers' lives, beginning even before they enter formal courses to prepare for teaching, and goes through entry into the career until retirement reaches its peak. In this context, the different experiences lived by teachers significantly influence their learning, practices and professional development. In view of this, the main objective of this research was to identify and analyze, through the narratives and productions prepared by a Basic Education teacher during her participation in three training initiatives at UFSCar, the teacher's training and professional trajectory, as well as the impacts of these moments in their professional development. Qualitative in nature, this is an exploratory research, in which the data analyzed refer to the narratives and productions developed by a Basic Education teacher during participation in different training initiatives in the context of the Federal University of São Carlos- UFSCar. The theoretical framework is supported by discussions about the teaching profession and teacher training; teaching professional development and teaching learning and induction and mentoring programs, with the main authors: Shulman; Mizukami; Nóvoa; Reali; Tancredi; Marcelo Garcia; Huberman, among others. Data analyzes were developed based on longitudinal and transversal strategies as a way of studying, interpreting and more comprehensively understanding the data and information collected, with the aim of explaining the context of the phenomenon as a whole. The analyzes highlight Professor Ananda's professional development as a continuous and multifaceted process that encompasses a wide range of experiences and learning throughout her teaching career. Professor Ananda underwent diverse training and practices that enabled her to build essential knowledge and skills for her training, development and professional practice. Regarding the main challenges faced and difficulties felt by the teacher, we realized that they were related to different moments and areas, social, professional and personal. Furthermore, the data indicated that the impacts promoted on the professional development of teacher Ananda, promoted from the various experiences, were signaled both in the theoretical knowledge and in the professional practice of the teacher.